Penerapan Prinsip-Prinsip Good Corporate Governance dan Corporate Social Responsibility di Hotel Grahadi Kuta - Pramita, I Gusti Ayu Adnya; Asri Dwija Putri, I Gusti Ayu Made (E-Jurnal Akuntansi; Vol 31 No 4 (2021), 2021)
GCG and CSR in the tourism sector especially in the hotels industries do not show a significant development compared to other business sectors. Since hotels are using natural resources and involving the community to support their business, therefore it is necessary for hotel industries to implement GCG within their internal management as well as implementing their social responsibilities for the public. This study.aims to determine the implementation of GCG and CSR principles at Grahadi Hotel Kuta Bali. Data in this study were obtained through interviews with informants namely GM, HRD and accounting staff. Data generated in the form of manuscripts from in-depth interviews. The research method used is descriptive qualitative. Findings of this research showed that: 1) the implementation of the GCG principles of Grahadi Kuta Bali Hotel is in accordance with the 5 GCG principles. 2) The implementation of CSR Grahadi Kuta Hotel is in accordance with the Triple Bottom Line principle.  Keywords: Implementation; GCG Principles; CSR Principles; Grahadi Hotel.